1995
DOI: 10.1007/bf02310358
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relatedness of strains ofMycobacterium avium using pulsed-field gel electrophoresis

Abstract: The application of molecular techniques to investigate strain relatedness may help define the local epidemiology of Mycobacterium avium infection, and, by identifying false isolates (i.e. neither pathogens nor colonizers) resulting from contamination, may serve as a tool for quality control in the laboratory. For this purpose, isolates from all patients (n = 129) with Mycobacterium avium infections identified over a two-year period were investigated by pulsed-field gel electrophoresis (PFGE). Of 38 PFGE patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…PFGE and AFLP analysis of M. kansasii are particularly useful because they reveal polymorphisms within each cluster. Mycobacterial strain characterization by PFGE has been previously demonstrated to be useful for epidemiological studies to trace sources of contamination and delineate outbreaks (4,8,16,29,34). Variations in the array of LRFs in both size and number may be due to sequence rearrangements, insertion or deletion of DNA, or base substitution within the restriction sites (25).…”
Section: Discussionmentioning
confidence: 99%
“…PFGE and AFLP analysis of M. kansasii are particularly useful because they reveal polymorphisms within each cluster. Mycobacterial strain characterization by PFGE has been previously demonstrated to be useful for epidemiological studies to trace sources of contamination and delineate outbreaks (4,8,16,29,34). Variations in the array of LRFs in both size and number may be due to sequence rearrangements, insertion or deletion of DNA, or base substitution within the restriction sites (25).…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterial DNA plugs were prepared as previously described (54) with the following modifications. Ampicillin and D-cycloserine were added to the culture 24 h prior to harvesting at final concentrations of 0.1 and 1.0 mg/ml, respectively (8). The step requiring vortexing of the cells in the presence of 3-mm glass beads was omitted, and the Bio-Rad Genepath wash solution was replaced with TE buffer (10 mM Tris, 1 mM EDTA [pH 8.0]).…”
Section: Methodsmentioning
confidence: 99%
“…Using a DNA probe consisting of IS900 and linked chromosomal DNA, it was shown that European and U.S. M. avium isolates share an RFLP pattern whereas isolates from Africa share a different pattern (398). LRF patterns have also been used as a quality control tool in a clinical mycobacteriology laboratory and as a tool for distinguishing true outbreaks of M. avium complex infection from pseudo-outbreaks due to laboratory-associated contamination (63).…”
Section: Characteristics Of the M Avium Complexmentioning
confidence: 99%